Public involvement and engagement in primary and emergency care research: the story from PRIME Centre Wales. (2020) - Evans, Bridie Angela; Gallanders, John; Griffiths, Lesley; Harris-Mayes, Robert; James, Mari; Jones, Sian; Williams, Natalie Joseph; Nettle, Mary; Rolph, Martin; Snooks, Helen; Wallace, Carolyn; Edwards, Adrian
No abstract available